دراسة حول إنتاج الهيدروجين باستخدام الطاقة الشمسية - اسحيمي, شهيرة; بن دومة, سكينة (university of eloued جامعة الوادي, 2023)
في هذا العمل تم التطرق إلى مفاهيم عامة حول الطاقة الشمسية والألواح الكهروضوئية وكيفية صناعتها وأنواعها. وتم التعرف أيضا على خصائص غاز الهيدروجين وأنواعه وطرق إنتاجه. من بينها التحليل الكهربائي بواسطة تقنية PEM المسؤولة عن فصل جزيء الماء إلى هيدروجين وأكسجين. كما تم تطبيق عدة تجارب قصد إنتاج غاز الهيدروجين من الماء المقطر بواسطة الطاقة الشمسية، الجهاز المستخدم يحتوي على خمس وحدات: وحدة حمل، وحدة قياس، لوح شمسي، محلل كهربائي وخلية وقود يعملان بتقنية PEM . تمت أيضا دراسة كفاءة اللوح الشمسي والمحلل فلوحظ أن هناك علاقة طردية بين الإشعاع الشمسي الساقط وتدفق غاز الهيدروجين المنتج، كذلك لوحظ زيادة حجم الغاز المنتج مع مرور الزمن.In this work, general concepts about solar energy and photovoltaic panels, their manufacturing processes, and types were addressed. Additionally, an introduction to the properties of hydrogen gas, its types, and production methods was provided. Among these methods is the electrochemical analysis using the PEM (Proton Exchange Membrane) technology, responsible for separating water molecules into hydrogen and oxygen. Several experiments were conducted to produce hydrogen gas from distilled water using solar energy. The device used consisted of five units: a load unit, a measurement unit, a solar panel, an electrical analyzer, and a fuel cell, all operating with PEM technology. The efficiency of the solar panel and the analyzer was also studied, and it was observed that there is a direct relationship between incident solar radiation and the flow of produced hydrogen gas. Additionally, an increase in the volume of the gas produced over time was observed
مذكرة ماستر فيزياء
Keywords: الهيدروجين الشمسي، تقنية PEM ، الطاقة الشمسية، اللوح الشمسي، خلايا الوقود.; Solar hydrogen, PEM technology, solar energy, solar panel, fuel cells..